2000
DOI: 10.1017/s0952523800174036
|View full text |Cite
|
Sign up to set email alerts
|

In search of the visual pigment template

Abstract: Absorbance spectra were recorded by microspectrophotometry from 39 different rod and cone types representing amphibians. reptiles, and fishes, with A1- or A2-based visual pigments and lambdamax ranging from 357 to 620 nm. The purpose was to investigate accuracy limits of putative universal templates for visual pigment absorbance spectra, and if possible to amend the templates to overcome the limitations. It was found that (1) the absorbance spectrum of frog rhodopsin extract very precisely parallels that of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,085
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 959 publications
(1,121 citation statements)
references
References 62 publications
22
1,085
1
1
Order By: Relevance
“…Cells were harvested before isolating rhodopsin photopigments by affinity immunochromatography and binding to excess 11-cis retinal in the dark. 19,20 Dark and bleached absorbance spectra were recorded using a UV-visible spectrophotometer, and the peak sensitivity value, the lambda max (λ max ), was determined by fitting to a standard rhodopsin template 21 as previously described 19,20 (Supplementary Materials and Methods online).…”
Section: Construct Generationmentioning
confidence: 99%
“…Cells were harvested before isolating rhodopsin photopigments by affinity immunochromatography and binding to excess 11-cis retinal in the dark. 19,20 Dark and bleached absorbance spectra were recorded using a UV-visible spectrophotometer, and the peak sensitivity value, the lambda max (λ max ), was determined by fitting to a standard rhodopsin template 21 as previously described 19,20 (Supplementary Materials and Methods online).…”
Section: Construct Generationmentioning
confidence: 99%
“…These measurements were made at four different flicker rates, ranging from 10 to 25 Hz. Each pair of the sensitivity values obtained from this procedure was best fitted using standard photopigment absorption curves (Govardovskii et al 2001) with the k max values determined to the nearest 0.1 nm. The logic of the experiment was that if the 510 nm peak value obtained earlier reflected mostly contributions from rods, then those signals should become progressively attenuated at higher flicker rates, i.e., one should see a Purkinje shift.…”
Section: Erg Measurementsmentioning
confidence: 99%
“…The rhodopsin and metarhodopsin spectra used in the calculations were obtained with the visual pigment template of Govardovskii et al (2000), where spectral shape is fully determined by the wavelength of maximal absorption. Calculations with visual pigment spectra peaking at slightly different wavelengths demonstrated that the anomalous effects of Fig.…”
Section: Blue Visual Pigmentmentioning
confidence: 99%